THE INFLUENCE OF BRITISH ROMANTIC POETS ON EARLY INDIAN ENGLISH POETRY: A COMPARATIVE STUDY - Rani, Monika (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The present research paper is an investigation into the influences of the British romantic poets like Wordsworth, Coleridge, Byron, Shelley and Keats on the early Indian English poets in the 19 th century and the early 20 th century. It shows the differences and similarities of the poetic themes, styles, and philosophical thoughts. The dissimilarity of the poets such as Henry Derozio, Toru Dutt and Sarojini Naidu provides the comparative approach to the study of their work. It concludes that British Romanticism had a significant influence on the development of Indian English poetry and stimulated the expression of emotions, nature, and freedom-love, but the Indian poets also Indianized these influences to make them fit in the Indian conditions and culture.